The Influence of Inquiry Training Learning Model Based Design Thinking on Creative Thinking Skills of Indonesia Students: Systematic Literature Review and Meta-analysis - Yuyun Suprapto; Asmawati Asmawati; Abdul Rahman; Wasito Utomo; Tomi Apra Santosa (Postgraduate, University of Mataram, 2023)
The purpose of this study is to determine the influence of the design thinking-based inquiry training learning model on the creative thinking skills of students in Indonesia.Â This type of research is a type of systematic literature review (SLR) research and meta-analysis.Â The sources in this study analyzed 13 studies obtained through the databases of Google Scholar, Education Resources Information Center (ERIC), Wiley, PLoL ONE, Taylor of Francis, and IEEE published from 2019-2023. Analyze data with the help of JSAP applications. The results concluded that the summary effect size value (rE = 0.84; p < 0.001) high effect size category. This finding shows that the inquiry training learning model based on design thinking has a high positive effect on the creative thinking ability of students in Indonesia